Spór o człowieka: Wissarion Bieliński i Mikołaj Gogol. O dwóch modelach literackiego kodowania rzeczywistości - Abassy, Małgorzata (Wydawnictwo Naukowe UAM, 2012)
The aim of this paper is to conduct a comparative analysis of two culture codes, semantic and asemantico-asyntactic, as tools for ordering reality and discovering the meaning of events. Belinsky and Gogol’s lives and their mutual relations are the subject of our research. The antinomy, and even irreconcilability of codes is observed in concepts of the human and the world. According to the semantic code which was used by Gogol, a person is a part and, at the same time, a reflection of God’s order, and the world is dichotomic (sacral – sinful, meaningful – meaningless, spiritual – material); it is an area for the fight between good and evil. Belinski, in turn, following the asemantico-asyntactic code, put the human at the centre of the rational world. At the beginning of the 40’s, when Belinsky could still interpret Gogol’s writings within the frameworks of asyntactico-asemantic culture code, he regarded himself as similar to Gogol. The split occurred after the book Chosen pieces of a correspondence with friends was published. The tragedy of not being understood, which both great Russian thinkers faced, was evidence for the existence of two separate sign and meaning systems within one culture. It must be added that the systems developed against the background of state order, which was coded by the syntactic culture code. Further research needs to be conducted in this field.
The human as a subject of discussion: Wissarion Belinsky and Nikolay Gogol. About two models of literary encoding of reality
Keywords: Gogol; Belinsky; Culture codes; Russia; Lotman; Literature